Using Pictures in Improving the Speaking Ability of the Grade Eight-A Students of SMP Negeri 1 Anggana - Karsono, Puguh (Dinamika Ilmu, 2014)
The objectives of this study were to know the speaking ability of the Grade Eight-A Students of SMP Negeri 1 Anggana in Academic Year 2012/2013 after using Pictures, and to know the student’s participation of the grade Eight-A students of SMP Negeri 1 Anggana in Academic Year 2012/ 2013 through pictures. This study employed CAR (Classroom Action Research) design. The procedures of CAR, i,e. Planning, acting, observing and reflecting. The result showed that the use of pictures had succeeded, to some extent, to improve student’s speaking ability and students’ participation. The student’s speaking ability improve as it showed that the number of students which were classified as good and very good' improved from 6, 4% in preliminary study to 83, 9% in cycle I and became 100% in cycle 2. While those who classified as fair and poor reduced from 93, 6% in preliminary study to 16, 1% in cycle 1 and became 0% in cycle 2. As a result, the using of pictures could enhance the students' speaking ability. Mostly, the students could improved their fluency, content, pronunciation and grammar. The average score raised from 66 in preliminary study, 74 in cycle 1, and 80 in cycle 2. The students’ participation also improved from cycle to cycle. In cycle 1, during the teaching learning process, the class VIII-A had an improvement. It stated that from meeting 1 to 3, the students were actively involved. The result had changed in meeting 3 where 13 students were categorized as very active and 12 students were active enough in presenting the pictures and made progress every meeting. The rest 4 students were categorized as hesitant and 2 students were not active since they were still shy to explore their ideas. On the other hand, during 3 meetings started from meeting 4 to 6 in cycle 2, the class VIII-A also had more improvement than what they did in cycle 1. There were 22 students categorized as very active and 8 students were active enough. The result of the research showed that the implementation of using picture media could give an improvement on students' speaking ability and students’ participation.